Adoption of Innovation in Segregated Construction Project - Rakhmat Fitranto Aditra; Agus S. Ekomadyo (RUAS, 2021)
The development in construction industry in recent times show the tendency of segregation in industrialization process. This research observes the segregation phenomenon of  innovation adoption on small scale construction project as like as segregation phenomenon of construction industry at common. Case study in this research is Musholatorium, which is an abbreviation of Mushola (prayer room) with planetarium, in Lembang Bandung. The innovation on this research was the geodesic dome structure as a Musholatorium. The method used in this research consisted of: (a) describing the project and (b) analysis. The project process consisted of (a) initiation, (b) architectural design, (c) component design, and (d) component fabrication and construction. From the analysis, it could be suggested that there are inefficiencies of knowledge distribution during the project process since the knowledge was transferred without sufficient collaboration. Only the owner involved during the whole process and could actually conclude the whole to develop the innovation. The nature of construction project, which usually be segmented, caused the inter-discipline aspect hard to be communicated between actors. In order to introduce innovation into building construction project, it is important for the actors to involve and collaborate inside the projects as a collective works.